Circulating CXCL9, monocyte percentage, albumin, and C-reactive protein as a potential, non-invasive, molecular signature of carotid artery disease in 65+ patients with multimorbidity: a pilot study in Age.It - Capri, Miriam; Fronterrè, Sara; Collura, Salvatore; Giampieri, Enrico; Carrino, Sara; Feroldi, Francesca Maria; Ciurca, Erika; Conte, Maria; Olivieri, Fabiola; Ullo, Ines; Pini, Rodolfo; Vacirca, Andrea; et al. (Frontiers in Endocrinology, 2024)
Background. Carotid endarterectomy (CEA) for the prevention of upcoming vascular and cerebral events is necessary in patients with high-grade stenosis (≥ 70%). In the framework of the Italian National project Age.It, a pilot study was proposed aiming at the discovery of a molecular signature with predictive potential of carotid stenosis comparing 65+ asymptomatic and symptomatic inpatients.Methods. Forty-two inpatients have been enrolled, including 26 males and 16 females, with mean age 74 ± 6. Sixteen symptomatic and 26 asymptomatic inpatients with ≥70% carotid stenosis underwent CEA, according to the recommendations of the European Society of Vascular Surgery and the Society of Vascular Surgeons. Plaque biopsies and peripheral blood samples from the same individuals were obtained. Hematobiochemical analyses were conducted on all inpatients and plasma cytokines/molecules, such as IL-6, sIL-6Ralpha, sgp130, myostatin (GDF8), Follistatin, Activin A, CXCL9, FGF21 and Fibronectin, were measured using the ELISA standard technique. MiR-profiles were obtained in the discovery phase including 4 symptomatic and 4 asymptomatic inpatients (both plasma and plaque samples), testing 734 miRs. MiRs emerging from the profiling comparison were validated through RT-qPCR analysis in the total cohort. Results and conclusion. The two groups of inpatients differ in the expression levels of blood c-miRs-126-5p and -1271-5p (but not in their plaques), which are more expressed in symptomatic subjects. Three cytokines resulted significant between the two groups: IL-6, GDF8 and CXCL9. Using Receiver-Operating Characteristic (ROC) analysis with a machine learning-based approach, the most significant blood molecular signature encompasses albumin, Creactive protein (CRP), the percentage of monocytes and CXCL9, allowing the distinction of the two groups (AUC = 0.83, p = 0.0028). The potential of the molecular signature will be tested in a second cohort of monitored patients allowing the application of a predictive model and the final evaluation of cost/benefit for an assessable screening test.